A sludge treatment slow-release material and treatment method
By coating iron-carbon microelectrolytic filler water-soluble coating materials and persulfate to form sustained release materials, the problem of removing various pollutants in the sludge is solved, and the effect of long-term sludge repair is achieved, and the environmental secondary effect is avoided pollute.
Patent Information
- Application Number
- CN202410911230.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-09
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-07-09
AI Technical Summary
Existing sludge treatment technology is difficult to effectively remove a variety of pollutants in sludge, and microbial treatment agents are difficult to apply for long-term results, resulting in poor sludge treatment and may cause secondary environmental pollution.
A water-soluble coating material and persulfate coated with iron-carbon microelectrolytic filler is used to form a sustained release material. When the material is added to the sludge, the water-soluble coating material dissolves, and the iron-carbon microelectrolytic filler is slowly released to form a primary cell, producing stable divalent iron ions, and catalyzed the removal of nitrogen-containing, phosphorus-containing organic matter and heavy metals in the sludge.
It realizes long-term removal of various pollutants in the sludge, extends the treatment time of sustained-release materials, avoids secondary environmental pollution, and is simple in process and easy to obtain raw materials.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sludge treatment, and relates to a sludge treatment slow-release material and a treatment method. Background Art
[0002] With the improvement of the level of modern industry, the output of sludge has also increased dramatically. Sludge contains a variety of pollutants such as ammonia nitrogen, COD and heavy metal ions, which lead to water imbalance and affect the survival of aquatic plants and animals. At the same time, heavy metal ions and their compounds in sludge will be enriched in fish and other aquatic organisms, and will cause serious harm to humans and the surrounding ecological environment through the circulation of drinking water and food chains. At the same time, if the sludge is not handled properly, it will cause secondary pollution to the environment, further threatening the ecological environment and human health.
[0003] At present, the main treatment methods for pollutants in sludge are chemical method, biological method and advanced oxidation method. The chemical method is to add drugs to the sludge to achieve the purpose of purifying water quality. However, due to the variety of pollutants in the sludge, many treatment agents are difficult to remove pollutants and the purification effect is poor. The biological method is to achieve the purification effect by adding certain microbial agents to the sludge multiple times, but this kind of microorganisms directly added to the sludge exist in a free form, resulting in serious loss and unable to work in the sludge for a long time. Advanced oxidation method is widely used due to its strong oxidation ability, thorough reaction, short reaction time and small footprint.
[0004] Iron-carbon micro-electrolysis is a treatment technology widely used in dye wastewater, petrochemical wastewater, pharmaceutical wastewater, etc. The principle of iron-carbon micro-electrolysis materials to treat wastewater is based on the redox reaction of the primary cell. The anode undergoes an oxidation reaction, and the zero-valent iron is oxidized to divalent iron ions; the cathode undergoes a reduction reaction, and the hydrogen ions are reduced to hydrogen. Divalent iron ions will undergo an oxidation reaction with multiple components in the wastewater to generate iron ions. The hydrate of iron ions has a strong adsorption-flocculation activity and can adsorb a large amount of tiny particles in the wastewater to achieve the purpose of purifying the wastewater. However, when iron-carbon micro-electrolysis materials are used to treat wastewater, the iron-carbon micro-electrolysis materials are usually loaded into a decontamination device, and the wastewater is treated during the flow of wastewater. However, due to the high concentration of sludge, it is not easy to pass through the decontamination device, and the removal of pollutants in the sludge cannot be achieved. Summary of the invention
[0005] Based on the above technical problems to be solved, the purpose of the present invention is to provide a sludge treatment slow-release material and a treatment method.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] The invention provides a sludge treatment slow-release material. The raw materials for preparing the slow-release material include: an iron-carbon micro-electrolysis filler, a water-soluble coating material and persulfate. The water-soluble coating material is coated on the surface of the iron-carbon micro-electrolysis filler.
[0008] In the present application, a water-soluble coating material is coated on the surface of an iron-carbon micro-electrolysis filler to form a slow-release film. When the iron-carbon micro-electrolysis filler coated with a slow-release film is added to the sludge, the water-soluble coating material slowly dissolves under the dissolution of sewage in the sludge, and then the iron-carbon micro-electrolysis filler slowly contacts the sludge. In the sludge, there is a potential difference between the zero-valent iron and carbon in the iron-carbon micro-electrolysis filler. With iron and carbon serving as anode and cathode respectively, countless tiny primary cells are formed in the sewage in the sludge. In these primary cells, an oxidation reaction occurs at the anode, and the zero-valent iron is oxidized to divalent iron ions; a reduction reaction occurs at the cathode, and the hydrogen ions are reduced to hydrogen gas.
[0009] The divalent iron ions produced in the primary cell can be used as a catalyst for persulfate, catalytically activating persulfate to produce persulfate radicals and trivalent iron ions. Among them, the persulfate radicals can oxidize nitrogen-containing organic matter in the sludge, thereby achieving the purpose of removing nitrogen-containing organic matter in the sludge. Since the iron-carbon micro-electrolysis filler is slowly released under the coating effect of the water-soluble coating material, the primary cell formed by the iron-carbon micro-electrolysis filler can continuously produce stable divalent iron ions, prolong the active time of persulfate, and then prolong the treatment time of the slow-release material on the sludge, achieving the purpose of long-term repair.
[0010] In addition, the trivalent iron ions produced by the catalytic activation of persulfate by divalent iron ions can react with phosphates in the sludge to form iron phosphate precipitation, thereby achieving the purpose of removing phosphorus-containing organic matter in the sludge. The water-soluble coating material dissolved in the sludge can also complex with heavy metals in the sludge to achieve the purpose of removing heavy metals.
[0011] In the present application, the persulfate is sodium persulfate or potassium persulfate. The water-soluble coating material includes any one of cyclodextrin, pretreated starch and sodium caseinate, wherein the pretreated starch is gelatinized starch.
[0012] In the present application, the mass ratio of the iron-carbon micro-electrolysis filler, the water-soluble coating material and the persulfate is 1:(2-5):(0.5-1). More preferably, the mass ratio of the iron-carbon micro-electrolysis filler, the water-soluble coating material and the persulfate is 1:4:1.
[0013] Furthermore, the raw material for preparing the sustained-release material in the present application also includes polylactic acid, wherein the mass ratio of polylactic acid to the water-soluble coating material is 1:(2-10). Preferably, the mass ratio of polylactic acid to the water-soluble coating material is 1:5.
[0014] Polylactic acid is a new type of biodegradable material that can be completely degraded by microorganisms in nature, eventually generating carbon dioxide and water without polluting the environment. When polylactic acid and a water-soluble coating material are used to simultaneously coat the iron-carbon micro-electrolysis filler to form a sustained-release membrane, the surface of the iron-carbon micro-electrolysis filler is interspersed with polylactic acid and a water-soluble coating material. Since the water-soluble coating material dissolves in the sewage in the sludge, while polylactic acid does not dissolve in the sewage in the sludge, the thicker parts of the water-soluble coating material in the sustained-release membrane are first dissolved, and part of the iron-carbon micro-electrolysis filler is exposed in the sludge, and a primary cell is generated. When the iron-carbon micro-electrolysis filler exposed in the sludge has completely reacted, the sewage in the sludge will penetrate into the sustained-release layer through the iron-carbon micro-electrolysis filler, and then dissolve the water-soluble coating material in other parts of the sustained-release layer, so that more iron-carbon micro-electrolysis fillers are exposed in the sludge. Therefore, the coating arrangement of polylactic acid and water-soluble coating material can make the water-soluble coating material dissolve slowly, and then make the iron-carbon micro-electrolysis filler release slowly, so as to achieve the purpose of long-term repair of sludge.
[0015] The present application provides a sludge treatment method, the method comprising:
[0016] S01: After the water-soluble coating material is completely dissolved in water, the iron-carbon micro-electrolysis filler is added and stirred evenly to form a mixture.
[0017] S02: The mixture is concentrated by evaporation and vacuum dried to obtain coated particles.
[0018] The mixture is evaporated and concentrated while being stirred, and the evaporated and concentrated product is vacuum dried to form coated particles, wherein the evaporation and concentration temperature is 110-120°C, and the drying temperature is 150-160°C.
[0019] S03: The coated particles and the persulfate are evenly mixed to form a sludge treatment slow-release material;
[0020] S04: adding the sludge treatment slow-release material to the sludge at room temperature, and stirring to mix well;
[0021] S05: Allow the sludge to stand for 2-3 months and after testing whether the sludge has been repaired to the standard, adjust the pH value of the sludge to neutral.
[0022] In addition, the present application also provides another sludge treatment method, which comprises:
[0023] S01: dissolving polylactic acid and a water-soluble coating material in N,N-dimethylformamide, mixing them evenly, and then subjecting them to high pressure homogenization to form a mixed solution;
[0024] S02: adding iron-carbon micro-electrolysis filler to the mixed solution, stirring evenly to form a mixture;
[0025] S03: The mixture is concentrated by evaporation and vacuum dried to obtain coated particles;
[0026] The mixture is evaporated and concentrated while being stirred, and the evaporated and concentrated product is vacuum dried to form coated particles, wherein the evaporation and concentration temperature is 160-170°C, and the drying temperature is 180-200°C.
[0027] S04: the coated particles and the persulfate are evenly mixed to form a sludge treatment slow-release material;
[0028] S05: adding the sludge treatment slow-release material to the sludge at room temperature, and stirring to mix well;
[0029] S06: Allow the sludge to stand for 2-3 months and after testing whether the sludge has been repaired to the required standard, adjust the pH value of the sludge to neutral.
[0030] The present invention has the following beneficial effects:
[0031] (1) The use of water-soluble coating materials forms a slow-release film on the surface of the iron-carbon micro-electrolysis filler. As the water-soluble coating material continues to dissolve in the sludge, the iron-carbon micro-electrolysis filler is continuously released, continuously forming countless tiny primary cells, and then continuously generating stable divalent iron ions, thereby extending the active period of persulfate, and ultimately extending the treatment time of the slow-release material on the sludge, achieving the purpose of long-term repair.
[0032] (2) Divalent iron ions catalyze the activation of persulfate to produce persulfate free radicals and trivalent iron ions. Among them, persulfate free radicals can oxidize nitrogen-containing organic matter in the sludge, thereby achieving the purpose of removing nitrogen-containing organic matter in the sludge. Trivalent iron ions react with phosphate in the sludge to produce iron phosphate precipitates, thereby achieving the purpose of removing phosphorus-containing organic matter in the sludge.
[0033] (3) The use of polylactic acid and water-soluble coating materials enables the surface of the iron-carbon micro-electrolysis filler to be coated to form a slow-release film. The parts of the slow-release film where the water-soluble coating material is thicker are first dissolved completely, so that part of the iron-carbon micro-electrolysis filler is exposed in the sludge and a primary cell is generated. When the iron-carbon micro-electrolysis filler exposed in the sludge has completely reacted, the sewage in the sludge will penetrate into the slow-release layer through the iron-carbon micro-electrolysis filler, and then dissolve the water-soluble coating material in other parts of the slow-release layer, so that more iron-carbon micro-electrolysis filler is exposed in the sludge. Therefore, the coating setting of polylactic acid and water-soluble coating materials can cause the water-soluble coating material to dissolve slowly, and then cause the iron-carbon micro-electrolysis filler to be slowly released, thereby achieving the purpose of long-term repair of sludge.
[0034] (4) The water-soluble coating material dissolved in the sludge can also complex with the heavy metals in the sludge to achieve the purpose of removing heavy metals.
[0035] (5) The preparation process of the sustained-release material is simple, the raw materials are easily available, and it can continuously treat sludge with good sludge treatment effect. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is further explained and illustrated by means of specific embodiments below.
[0037] Example 1
[0038] An embodiment of the present application provides a sludge treatment slow-release material, wherein the raw materials for preparing the slow-release material include iron-carbon micro-electrolysis filler, cyclodextrin and sodium persulfate in a mass ratio of 1:4:1.
[0039] The method for treating the sludge treatment slow-release material comprises:
[0040] S101: After completely dissolving cyclodextrin in water, add iron-carbon micro-electrolysis filler and stir evenly to form a mixture.
[0041] S102: The mixture is evaporated and concentrated while being stirred, and the evaporated and concentrated product is vacuum dried to form coated particles, wherein the evaporation and concentration temperature is 110°C and the drying temperature is 150°C.
[0042] S103: The coated particles are mixed evenly with sodium persulfate to form a sustained-release material.
[0043] Example 2
[0044] An embodiment of the present application provides a sludge treatment slow-release material, wherein the raw materials for preparing the slow-release material include iron-carbon micro-electrolysis filler, cyclodextrin and sodium persulfate in a mass ratio of 1:2:0.5.
[0045] The method for treating the sludge slow-release material is the same as that in Example 1, except that the evaporation concentration temperature is 110°C and the drying temperature is 150°C.
[0046] Example 3
[0047] An embodiment of the present application provides a sludge treatment slow-release material, wherein the raw materials for preparing the slow-release material include iron-carbon micro-electrolysis filler, cyclodextrin and sodium persulfate in a mass ratio of 1:5:1.
[0048] The method for treating the sludge slow-release material is the same as that in Example 1, except that the evaporation concentration temperature is 110°C and the drying temperature is 150°C.
[0049] Example 4
[0050] An embodiment of the present application provides a sludge treatment slow-release material, wherein the raw materials for preparing the slow-release material include iron-carbon micro-electrolysis filler, gelatinized starch and potassium persulfate in a mass ratio of 1:4:1.
[0051] The method for treating the sludge slow-release material is the same as that in Example 1, except that the evaporation concentration temperature is 120°C and the drying temperature is 160°C.
[0052] Example 5
[0053] An embodiment of the present application provides a sludge treatment slow-release material, wherein the raw materials for preparing the slow-release material include iron-carbon micro-electrolysis filler, gelatinized starch and potassium persulfate in a mass ratio of 1:4:1.
[0054] The method for treating the sludge slow-release material is the same as that in Example 1, except that the evaporation concentration temperature is 110°C and the drying temperature is 150°C.
[0055] Example 6
[0056] An embodiment of the present application provides a sludge treatment slow-release material, wherein raw materials for preparing the slow-release material include iron-carbon micro-electrolysis filler, sodium caseinate and potassium persulfate in a mass ratio of 1:4:1.
[0057] The method for treating the sludge slow-release material is the same as that in Example 1, except that the evaporation concentration temperature is 110°C and the drying temperature is 140°C.
[0058] Example 7
[0059] An embodiment of the present application provides a sludge treatment slow-release material, wherein the raw materials for preparing the slow-release material include iron-carbon micro-electrolysis filler, cyclodextrin, polylactic acid and sodium persulfate in a mass ratio of 1:20:4:1.
[0060] The method for treating the sludge treatment slow-release material comprises:
[0061] S701: dissolving polylactic acid and cyclodextrin in N,N-dimethylformamide, mixing them evenly, and then subjecting them to high pressure homogenization to form a mixed solution.
[0062] S702: Add iron-carbon micro-electrolysis filler to the mixed solution, stir evenly, and form a mixture.
[0063] S703: The mixture is evaporated and concentrated while being stirred, and the evaporated and concentrated product is vacuum dried to form coated particles, wherein the evaporation and concentration temperature is 160°C and the drying temperature is 180°C.
[0064] S704: The coated particles are mixed evenly with sodium persulfate to form a sustained-release material.
[0065] Example 8
[0066] An embodiment of the present application provides a sludge treatment slow-release material, wherein the raw materials for preparing the slow-release material include iron-carbon micro-electrolysis filler, cyclodextrin, polylactic acid and sodium persulfate in a mass ratio of 1:4:2:1.
[0067] The method for treating the sludge slow-release material is the same as that in Example 7, except that the evaporation concentration temperature is 170°C and the drying temperature is 200°C.
[0068] Example 9
[0069] An embodiment of the present application provides a sludge treatment slow-release material, wherein the raw materials for preparing the slow-release material include iron-carbon micro-electrolysis filler, gelatinized starch, polylactic acid and potassium persulfate in a mass ratio of 1:20:2:0.5.
[0070] The method for treating the sludge slow-release material is the same as that in Example 7, except that the evaporation concentration temperature is 160°C and the drying temperature is 190°C.
[0071] Example 10
[0072] An embodiment of the present application provides a sludge treatment slow-release material, wherein the raw materials for preparing the slow-release material include iron-carbon micro-electrolysis filler, sodium caseinate, polylactic acid and potassium persulfate in a mass ratio of 1:9:3:0.5.
[0073] The method for treating the sludge slow-release material is the same as that in Example 7, except that the evaporation concentration temperature is 160°C and the drying temperature is 190°C.
[0074] Comparative Example 1
[0075] The comparative example of the present application provides a sludge treatment slow-release material, and the raw materials for preparing the slow-release material include iron-carbon micro-electrolysis filler, cyclodextrin, polylactic acid and sodium persulfate in a mass ratio of 1:5:15:0.5.
[0076] In order to verify that the sludge treatment slow-release material provided in the examples of the present application can slowly treat sludge, the slow-release materials prepared in Examples 1-10 and Comparative Example 1 were respectively placed in sludge of equal mass, and the time when the sludge degradation rate reached 90% was recorded, and Table 1 was obtained.
[0077] Table 1: Time required for the degradation rate of sludge by the slow-release materials prepared in Examples 1-10 to reach 90%
[0078]
[0079] It can be seen from Table 1 that when the sustained-release materials prepared in Examples 1-6 are used to treat sludge, the sustained-release material prepared in Example 3 has a longer sustained-release time. This is because a larger amount of water-soluble coating material is used in the sustained-release material and the sustained-release film is thicker, resulting in a longer sustained-release time for sludge treatment.
[0080] When the slow-release materials prepared in Examples 7-10 treat sludge, the slow-release time of the slow-release material prepared in Example 7 is longer. This is because the reasonable ratio of polylactic acid and water-soluble coating material enables the water-soluble coating material in the slow-release membrane to be completely dissolved and slowly dissolved, thereby causing the iron-carbon micro-electrolysis filler to slowly leak out, thereby slowly treating the sludge. The degradation rate of the slow-release material prepared in Comparative Example 1 for sludge did not reach 90%. This is because the content of polylactic acid in Comparative Example 1 is much greater than the content of cyclodextrin, resulting in a large amount of polylactic acid in the slow-release membrane. Polylactic acid is insoluble in water, so only a small part of cyclodextrin is soluble in water, which results in only a small part of the iron-carbon micro-electrolysis filler contacting with the sludge, producing a small amount of divalent iron ions, and the activity of catalytic activation of persulfate is greatly reduced, which ultimately leads to a greatly reduced sludge treatment efficiency.
[0081] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A sludge treatment slow-release material, characterized in that: The preparation raw materials include: iron-carbon micro-electrolysis filler, water-soluble coating material, polylactic acid and persulfate, wherein the water-soluble coating material and the polylactic acid are coated on the surface of the iron-carbon micro-electrolysis filler; the mass ratio of the iron-carbon micro-electrolysis filler, the water-soluble coating material and the persulfate is 1:(2-5):(0.5-1); the mass ratio of the polylactic acid to the water-soluble coating material is 1:(2-10); The preparation method of the sludge treatment slow-release material comprises: The polylactic acid and the water-soluble coating material are dissolved in N,N-dimethylformamide, mixed evenly, and then subjected to high pressure homogenization to form a mixed solution; Adding iron-carbon micro-electrolysis filler to the mixed solution, stirring evenly to form a mixture; The mixture is concentrated by evaporation and vacuum dried to obtain coated particles; The coated particles are evenly mixed with the persulfate to form a sludge treatment slow-release material.
2. The sludge treatment slow-release material according to claim 1, characterized in that: The water-soluble coating material includes any one of cyclodextrin, pretreated starch and sodium caseinate.
3. The sludge treatment slow-release material according to claim 1, characterized in that: The mass ratio of the iron-carbon micro-electrolysis filler, the water-soluble coating material and the persulfate is 1:4:
1.
4. The sludge treatment slow-release material according to claim 1, characterized in that: The mass ratio of the polylactic acid to the water-soluble coating material is 1:
5.
5. A sludge treatment method, characterized in that: The sludge treatment slow-release material according to any one of claims 1 to 4 is used, and the treatment method comprises: The polylactic acid and the water-soluble coating material are dissolved in N,N-dimethylformamide, mixed evenly, and then subjected to high pressure homogenization to form a mixed solution; Adding iron-carbon micro-electrolysis filler to the mixed solution, stirring evenly to form a mixture; The mixture is concentrated by evaporation and vacuum dried to obtain coated particles; The coated particles are evenly mixed with the persulfate to form a sludge treatment slow-release material; At room temperature, adding the sludge treatment slow-release material into the sludge, and stirring to mix well; After standing and curing for 2-3 months and testing whether the sludge has been repaired to the standard, the pH value of the sludge is adjusted to neutral.
6. The sludge treatment method according to claim 5, characterized in that: The temperature of the evaporation concentration is 160-170°C.
Citation Information
Patent Citations
Method for pre-treating organic industrial wastewater based on ferric-carbon micro-electrolysis activated persulfate
CN104891719A
Thermal power plant calcium carbonate sludge regeneration treatment agent and process
CN112142279A
Composite bioreactor based on iron-carbon carrier and preparation and sewage treatment method thereof
CN114835255A
Cited By
Low-carbon-source a2o biological pool iron-carbon micro-electrolysis filler, preparation method and application
CN122940278A